Word smart junior build a straight-A vocabulary - Heaton, Hayley; Princeton Review (Firm) (New York Random House, 2008)
An introduction to 500 words students should know by the time they enter high school. Uses stories to present words in context and has quizzes for reinforcement
Rev. ed. of: Word smart junior / C.L. Brantley. 2nd ed. 2002
1
Keywords: Vocabulary -- Juvenile literature